2015
DOI: 10.1111/peps.12115
|View full text |Cite
|
Sign up to set email alerts
|

Understanding The Curvilinear Relationships between LMX Differentiation and Team Coordination and Performance

Abstract: The leader-member exchange (LMX) literature argues that leaders develop different quality dyadic relationships with members in the same team (i.e., LMX differentiation). Research has generally not found support for a linear (i.e., main effect) relationship between LMX differentiation and team performance; rather, moderators typically determine whether the relationship is significantly positive or negative. Examining linear effect moderators alone, however, does not account for (a) potential curvilinear (i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 96 publications
(185 reference statements)
6
62
0
1
Order By: Relevance
“…The LMX measure developed in the western cultural context could suffer from potential cultural bias in one's interpretations of the social exchange phenomenon and therefore be vulnerable to cross‐cultural applications. Yet, there is empirical evidence supporting the use of LMX construct (as well as LMX differentiation and LLX constructs) across cultures, including the Chinese context (e.g., Carnevale, Huang, & Paterson, ; Huang, Xu, Huang, & Liu, ; Mackey, Huang, & He, in press; Sui et al, ; Zhou et al, ). Another concern is that there could be other contextual (e.g., collectivistic culture) or individual (e.g., traditionality) factors that might influence the way employees and their narcissistic leaders choose to interact in a leader–follower relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LMX measure developed in the western cultural context could suffer from potential cultural bias in one's interpretations of the social exchange phenomenon and therefore be vulnerable to cross‐cultural applications. Yet, there is empirical evidence supporting the use of LMX construct (as well as LMX differentiation and LLX constructs) across cultures, including the Chinese context (e.g., Carnevale, Huang, & Paterson, ; Huang, Xu, Huang, & Liu, ; Mackey, Huang, & He, in press; Sui et al, ; Zhou et al, ). Another concern is that there could be other contextual (e.g., collectivistic culture) or individual (e.g., traditionality) factors that might influence the way employees and their narcissistic leaders choose to interact in a leader–follower relationship.…”
Section: Discussionmentioning
confidence: 99%
“…We further propose that LMX differentiation in a group setting is likely to serve as a mediating mechanism through which leader narcissism indirectly influences follower voice. Prior LMX differentiation literature suggests that variability in LMX relationships within a group affects followers' psychological and behavioral outcomes (Erdogan & Bauer, ; Harris, Li, & Kirkman, ; Henderson, Wayne, Shore, Bommer, & Tetrick, ; Herdman et al, ; Liao, Liu, & Loi, ; Liden et al, ; Sui, Wang, Kirkman, & Li, ). Specifically, high LMX differentiation can be considered a dysfunctional condition discouraging employees from engaging in their jobs because it violates the norms of equality (Gooty & Yammarino, ; Herdman et al, ; Li & Liao, ).…”
Section: The Mediating Role Of Lmx Differentiationmentioning
confidence: 99%
“…Research has shown that a lack of leader monitoring efforts can cause a team to go into a purposeless situation, where members drift and ultimately lose track of their mission (Langfred, ; Larson & Callahan, ). When leaders put less effort into structuring team goals as well as into individual subgoals, it is also less likely that team members will synchronize their individual actions and sequence their contributions with team goal accomplishments (Sui, Wang, Kirkman, & Li, ). Without specific directions from the leader, team members may be unaware of situational changes occurring both inside and outside the team, or they may even interpret situational information erroneously.…”
Section: Studymentioning
confidence: 99%
“…7. Will neuroscience tools help to leverage the team's diverse capabilities to build a high--performance team [Sui et al 2016]? 8.…”
Section: Resultsmentioning
confidence: 99%